Modified 2-tuple Linguistic Neutrosophic Hybrid GRA Framework for Comprehensive Strength Evaluation for High-Quality Development in the Cultural Industry - Xiuhuan Feng; Yiran Feng; Xiaoyong Zhang; Shan Mi (Neutrosophic Sets and Systems)
The evaluation of comprehensive strength for the high-quality development of the cultural industry is a systematic assessment of the overall performance of the cultural sector across multiple dimensions. This evaluation covers aspects such as economic benefits, innovation capacity, social impact, cultural influence, and sustainability. By using both quantitative indicators and qualitative analysis, it measures the industry's overall competitiveness and growth potential, providing a scientific basis for policymaking, resource allocation, and industry optimization. This evaluation system helps promote high quality and sustainable growth in the cultural industry. The comprehensive strength evaluation for high quality development in the cultural industry is a multiple-attribute group decision-making (MAGDM) approach. In this study, entropy is put forward weight numbers along with 2-tuple linguistic neutrosophic sets (2TLNSs), and the 2-tuple linguistic neutrosophic number hybrid grey relational analysis (2TLNN HGRA) approach is put forward based on grey relational analysis (GRA) and 2TLNSs. Finally, a numerical example of comprehensive strength evaluation for high-quality development in the cultural industry was put forward and some comparisons are put forward to illustrate the 2TLNN-HGRA approach.